PARADIGMA NAHDLATUL ‘ULAMA TERHADAP MODERNISASI - Sunarto AS, A. (The Sociology of Islam, 2013)
Islam in Indonesia has been running quite unique, from the beginning of Islam so easy and quick to respond, ollowed by the public until after the battle of thought put Islam in the public sphere. So many conceptual contribution is expected to respond to the needs of people from vfarious Islamic thinkers, even by young Muslims. And in this paper, the authors also conducted an in-depth study to search the Islamic identity that can be felt responsive and grounded in the soil of Indonesia. Studies done by dissecting the religious rules, "al-muhafazhah 'ala al-qadim al-Salih al-akhdzu wa bi al-jadid al-ashlah" and produce a pattern of thinking that should Islamization is based on substantial study, contextual, rational, and the earthiness that gave birth to Islamic thought in Indonesia responsive. NU is an organization that seeks to hold the renewal and modernization in all fields. so with that, it is not always referred to as a traditional Islamic organization. Kata Kunci: Islam Indonesia, Identitas Islam, Organisasi, Modernisasi, Tradisional.